Advanced lung imaging and lung function testing in Ataxia-Telangiectasia - Alenazi, Saleh (2023)
Although a CT scan provides high-resolution images for lung, it involves use of ionising radiation, which in some patient groups might increase risk of cancer, for example, it increases the chances of malignancy in patients with ataxia telangiectasia (AT). Therefore, it is necessary to identify an alternative imaging modality for patients with AT and other patient groups with similar risks. Magnetic resonance imaging (MRI) is a potential alternative, but there are various obstacles to its use. MRI cannot produce high-resolution images of the lungs due to the lack of strong proton signals. However, over the last few decades, various developments in MRI have given glimmers of hope for high-quality lung imaging. Currently, there are three potential ways to image the lung using MRI: hyperpolarised noble gas MRI (129Xe), oxygen enhanced MR ventilation imaging (OE) and ultra-short echo time (UTE) proton imaging. Each of these methods has disadvantages and advantages but their use, either singly or in combination, has considerable potential. In this thesis, the potential to use OE-MRI has been assessed in patients with AT, because it is more readily available and inexpensive compared to hyperpolarised noble gas MRI. Moreover, it can provide temporal and spatial information compared to UTE technique, which provides only an anatomical image. Lung function can also be assessed using physiological measurements including spirometry and lung clearance index (LCI). In this thesis, spirometry, LCI and OE-MRI were assessed for their potential to provide useful information on lung function abnormalities in children with and without AT. The main conclusions were that children with AT find it difficult to perform spirometry and LCI to adequate standards, especially in the children aged over 11. Moreover, with further optimisation, oxygen-enhanced MRI might provide an alternative way of assessing lung abnormalities in this group of patients.